2022
DOI: 10.3390/agronomy12051165
|View full text |Cite
|
Sign up to set email alerts
|

Matter Production Characteristics and Nitrogen Use Efficiency under Different Nitrogen Application Patterns in Chinese Double-Cropping Rice Systems

Abstract: Panicle-stage nitrogen fertilizer is popular in parts of China due to its higher nitrogen recovery efficiency compared to basal and tiller nitrogen. However, the effect of conversion from basal to panicle-stage nitrogen on matter production, grain yield, and nitrogen use efficiencies (NUE) in Chinese double-cropping rice systems remains largely unknown. Here, we elucidate the effect by using two types of one-time basal nitrogen patterns (A and B), three panicle-N allocation patterns (C, D, and E), and the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…At 20 days after heading, increasing the proportion of fertilizers applied at the panicle and grain‐filling stages (N 2 ) increased the grain dry matter accumulation of the two cultivars under W 1 (Figure 3). The results indicate that the increase in the proportion of fertilizers applied at the panicle and grain‐filling stages promoted biomass allocation to the aboveground parts of rice plants under W 1 after heading, particularly biomass allocation to grains, which was significantly increased (W. T. Zhou et al., 2022). Therefore, a suitable increase in the proportion of fertilizers applied at the panicle and grain‐filling stages (N 2 ) effectively promoted the transport of nutrients to grains at 20 days after heading and allocated more energy to seed setting.…”
Section: Discussionmentioning
confidence: 97%
“…At 20 days after heading, increasing the proportion of fertilizers applied at the panicle and grain‐filling stages (N 2 ) increased the grain dry matter accumulation of the two cultivars under W 1 (Figure 3). The results indicate that the increase in the proportion of fertilizers applied at the panicle and grain‐filling stages promoted biomass allocation to the aboveground parts of rice plants under W 1 after heading, particularly biomass allocation to grains, which was significantly increased (W. T. Zhou et al., 2022). Therefore, a suitable increase in the proportion of fertilizers applied at the panicle and grain‐filling stages (N 2 ) effectively promoted the transport of nutrients to grains at 20 days after heading and allocated more energy to seed setting.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, under the same dense planting condition (D2, D3), the decrease of nitrogen fertilizer would reduce panicles per m 2 , but under the same nitrogen fertilizer condition, the increase in planting density would increase panicles per m 2 ( Table 3 ). It has also been suggested that increasing the number of rice plants appropriately without excess nitrogen application can achieve an increase in yield, which means that increasing density can increase yield [ 26 ]. Thus, the loss of panicles per m 2 caused by reduction can be compensated for by dense planting [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cultivation environment, including sowing date adjustment, nitrogen fertilization, and planting density management has already been adjusted to alleviate rice yield loss [ 25 , 26 , 27 ]. Enhancing rice yield components and promoting grain filling is the basis of high yields.…”
Section: Introductionmentioning
confidence: 99%